2022
DOI: 10.3390/ijerph191811646
|View full text |Cite
|
Sign up to set email alerts
|

Sixteen Years since the Convention on the Rights of Persons with Disabilities: What Have We Learned since Then?

Abstract: Persons with disabilities have historically been subjected to discrimination and exclusion, placing them in dangerous situations of social vulnerability. The Convention on the Rights of Persons with Disabilities, passed on the 13th of December 2006, was an important legislative landmark for valuing the rights of this population group. This study involved a bibliometric analysis of 1024 research articles published in Scopus on the social, workplace, educational, and financial inclusion of persons with disabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 111 publications
0
6
0
Order By: Relevance
“…Often, financial institutions have few customers with disabilities, perpetuating the belief that there is no necessity to develop financial services specifically tailored to their needs [ 15 , 16 ]. Furthermore, due to high unemployment rates among people with disability, banks, insurance providers, and other financial institutions do not consider them valuable clients [ 16 , 17 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Often, financial institutions have few customers with disabilities, perpetuating the belief that there is no necessity to develop financial services specifically tailored to their needs [ 15 , 16 ]. Furthermore, due to high unemployment rates among people with disability, banks, insurance providers, and other financial institutions do not consider them valuable clients [ 16 , 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…Many financially excluded individuals report that they do not go to banks because of geographical distance [ 45 ]. For people with disability this problem is accompanied by unfavourable physical environments and infrastructure, such as difficult terrains and inaccessible bank branches and ATMs [ 17 ]. Interventions are urgently required to improve the infrastructure and accessibility to banking services to accommodate the needs of people with disability.…”
Section: Potential Interventionsmentioning
confidence: 99%
“…The tendency of people with a recognised disability to evaluate practices and policies more positively than non-disabled participants could be related to their previous experiences in activities that have been socially less inclusive [ 43 ]. These individuals may have experienced situations in which they have not had the same opportunities as their peers, both in terms of specific practices, and in relation to regulations and policies that seek to promote equity and inclusion in the educational environment [ 44 ]. It is, therefore, possible that their more favourable assessment reflects a contrast between past experiences of exclusion and the current inclusion measures implemented, in the context of the study.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the exponential growth experienced between 2014 and 2015 was motivated by the approval of Directive 2014/95/UE and the United Nations 2030 Agenda, which has helped companies to see CSR as a business strategy to achieve sustainability. Other bibliometric studies in other areas of knowledge have already shown how regulation usually leads to the generation of greater scientific production [ 36 , [38] , [39] , [40] , 58 , 103 ].…”
Section: Conclusion and Discusionmentioning
confidence: 99%